Implementing Juvenile Justice Reform: The Federal Role - National Research Council (The National Academies Press, 2014)
In the past decade, a number of state, local, and tribal jurisdictions have begun to take significant steps to overhaul their juvenile justice systems - for example, reducing the use of juvenile detention and out-of-home placement, bringing greater attention to racial and ethnic disparities, looking for ways to engage affected families in the process, and raising the age at which juvenile court jurisdiction ends. These changes are the result of heightening awareness of the ineffectiveness of punitive practices and accumulating knowledge about adolescent development. Momentum for reform is growing. However, many more state, local, and tribal jurisdictions need assistance, and practitioners in the juvenile justice field are looking for guidance from the federal government, particularly from the Office of Juvenile Justice and Delinquency Prevention (OJJDP) in the Department of Justice. Implementing Juvenile Justice Reform identifies and prioritizes strategies and policies to effectively facilitate reform of the juvenile justice system and develop an implementation plan for OJJDP. Based on the 2013 report Reforming Juvenile Justice, this report is designed to provide specific guidance to OJJDP regarding the steps that it should take, both internally and externally, to facilitate juvenile justice reform grounded in knowledge about adolescent development. The report identifies seven hallmarks of a developmental approach to juvenile justice to guide system reform: accountability without criminalization, alternatives to justice system involvement, individualized response based on needs and risks, confinement only when necessary for public safety, genuine commitment to fairness, sensitivity to disparate treatment, and family engagement. Implementing Juvenile Justice Reform outlines how these hallmarks should be incorporated into policies and practices within OJJDP, as well as in actions extended to state, local, and tribal jurisdictions to achieve the goals of the juvenile justice system through a developmentally informed approach. This report sets forth a detailed and prioritized strategic plan for the federal government to support and facilitate developmentally oriented juvenile justice reform. The pivotal component of the plan is to strengthen the role, capacity, and commitment of OJJDP, the lead federal agency in the field. By carrying out the recommendations of Implementing Juvenile Justice Reform, the federal government will both reaffirm and advance the promise of the Juvenile Justice and Delinquency Prevention Act.
Keywords: Behavioral and Social Sciences

Promoting Positive Adolescent Health Behaviors and Outcomes: Thriving in the 21st Century - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Adolescence is a critical growth period in which youth develop essential skills that prepare them for adulthood. Prevention and intervention programs are designed to meet the needs of adolescents who require additional support and promote healthy behaviors and outcomes. To ensure the success of these efforts, it is essential that they include reliably identifiable techniques, strategies, or practices that have been proven effective. Promoting Positive Adolescent Health Behaviors and Outcomes: Thriving in the 21st Century identifies key program factors that can improve health outcomes related to adolescent behavior and provides evidence-based recommendations toward effective implementation of federal programming initiatives. This study explores normative adolescent development, the current landscape of adolescent risk behavior, core components of effective programs focused on optimal health, and recommendations for research, programs, and policies.
Keywords: Behavioral and Social Sciences; Health and Medicine

Fostering Healthy Mental, Emotional, and Behavioral Development in Children and Youth: A National Agenda - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Healthy mental, emotional, and behavioral (MEB) development is a critical foundation for a productive adulthood. Much is known about strategies to support families and communities in strengthening the MEB development of children and youth, by promoting healthy development and also by preventing and mitigating disorder, so that young people reach adulthood ready to thrive and contribute to society. Over the last decade, a growing body of research has significantly strengthened understanding of healthy MEB development and the factors that influence it, as well as how it can be fostered. Yet, the United States has not taken full advantage of this growing knowledge base. Ten years later, the nation still is not effectively mitigating risks for poor MEB health outcomes; these risks remain prevalent, and available data show no significant reductions in their prevalence. Fostering Healthy Mental, Emotional, and Behavioral Development in Children and Youth: A National Agenda examines the gap between current research and achievable national goals for the next ten years. This report identifies the complexities of childhood influences and highlights the need for a tailored approach when implementing new policies and practices. This report provides a framework for a cohesive, multidisciplinary national approach to improving MEB health.
Keywords: Behavioral and Social Sciences

Strengthening the Military Family Readiness System for a Changing American Society - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The U.S. military has been continuously engaged in foreign conflicts for over two decades. The strains that these deployments, the associated increases in operational tempo, and the general challenges of military life affect not only service members but also the people who depend on them and who support them as they support the nation – their families. Family members provide support to service members while they serve or when they have difficulties; family problems can interfere with the ability of service members to deploy or remain in theater; and family members are central influences on whether members continue to serve. In addition, rising family diversity and complexity will likely increase the difficulty of creating military policies, programs and practices that adequately support families in the performance of military duties. Strengthening the Military Family Readiness System for a Changing American Society examines the challenges and opportunities facing military families and what is known about effective strategies for supporting and protecting military children and families, as well as lessons to be learned from these experiences. This report offers recommendations regarding what is needed to strengthen the support system for military families.
Keywords: Behavioral and Social Sciences

Mental Health, Substance Use, and Wellbeing in Higher Education: Supporting the Whole Student - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Student wellbeing is foundational to academic success. One recent survey of postsecondary educators found that nearly 80 percent believed emotional wellbeing is a "very" or "extremely" important factor in student success. Studies have found the dropout rates for students with a diagnosed mental health problem range from 43 percent to as high as 86 percent. While dealing with stress is a normal part of life, for some students, stress can adversely affect their physical, emotional, and psychological health, particularly given that adolescence and early adulthood are when most mental illnesses are first manifested. In addition to students who may develop mental health challenges during their time in postsecondary education, many students arrive on campus with a mental health problem or having experienced significant trauma in their lives, which can also negatively affect physical, emotional, and psychological wellbeing. The nation's institutions of higher education are seeing increasing levels of mental illness, substance use and other forms of emotional distress among their students. Some of the problematic trends have been ongoing for decades. Some have been exacerbated by the COVID-19 pandemic and resulting economic consequences. Some are the result of long-festering systemic racism in almost every sphere of American life that are becoming more widely acknowledged throughout society and must, at last, be addressed. Mental Health, Substance Use, and Wellbeing in Higher Education lays out a variety of possible strategies and approaches to meet increasing demand for mental health and substance use services, based on the available evidence on the nature of the issues and what works in various situations. The recommendations of this report will support the delivery of mental health and wellness services by the nation's institutions of higher education.
Keywords: Health and Medicine; Education